2011
DOI: 10.1103/physrevb.83.115329
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion and interface growth in hafnium oxide and silicate ultrathin films on Si(001)

Abstract: Medium energy ion scattering (MEIS) has been used in combination with 16 O and 18 O isotope tracing to determine elemental depth distributions and elucidate oxygen transport in 2-5 nm thick HfO 2 and HfSiO x films grown by atomic layer deposition on Si(001). Both the oxygen isotope exchange rate in the dielectric as well as the interfacial silicon oxide growth rates were examined as a function of time, temperature, film stoichiometry (HfO 2 , HfSiO x and HfSiO x N y ) and crystallinity. The amount of exchanged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
(65 reference statements)
0
19
0
Order By: Relevance
“…Following PDA at 900 8C, a thicker IL was observed at the HfSiO/SiGe interface as compared that observed in the case of HfO 2 /SiGe. This was a result of the catalytic effect of phase separation in the partiallycrystallized HfSiO film [14][15][16]. In other words, the thicker IL in HfSiO film after PDA at 900 8C resulted from a large amount of O 2 inter-diffusion along the diffusion path by grain boundaries of partially crystallized HfO 2 compared to fully crystallized HfO 2 film with lack of grain boundary.…”
Section: Experimental Methodsmentioning
confidence: 90%
“…Following PDA at 900 8C, a thicker IL was observed at the HfSiO/SiGe interface as compared that observed in the case of HfO 2 /SiGe. This was a result of the catalytic effect of phase separation in the partiallycrystallized HfSiO film [14][15][16]. In other words, the thicker IL in HfSiO film after PDA at 900 8C resulted from a large amount of O 2 inter-diffusion along the diffusion path by grain boundaries of partially crystallized HfO 2 compared to fully crystallized HfO 2 film with lack of grain boundary.…”
Section: Experimental Methodsmentioning
confidence: 90%
“…• , the crystal direction [11][12][13][14][15][16][17][18][19][20][21][22][23], a direction with the same symmetry as the direction of the incoming beam, is seen as a dark spot. Two unwanted artifacts can also be seen.…”
Section: Angular Resolution: Channeling and Blocking Spectrummentioning
confidence: 99%
“…Electronic mail: marga@kth.se. b) Present address: HORIBA Jobin Yvon SAS, [16][17][18] Rue du Canal, 91165 Longjumeau Cedex, France. it was shown that the ToF concept in combination with a twodimensional detector was a useful way for MEIS analyzes. 8 This ToF concept introduces an additional degree of freedom in the diagnostics, making three-dimensional (3D) MEIS possible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from the characterization of the grown layers, in some of these oxide studies, oxygen diffusion through the gate dielectric towards deeper layers has also been investigated. 91,96,98,99,100,102,103 In addition, the thermodynamic stability in contact with Si of most of the mentioned binary oxides, has been evaluated. 32 All presented oxide materials have been considered as a replacement of the typical SiO2 gate dielectric layer, which exhibits high gate leakage current at small thicknesses (<1 nm), required for the continuous downscaling of microelectronics.…”
Section: Current Status 1231 Microelectronic (Dram and Cmos) Devicesmentioning
confidence: 99%